Joje Travel Sdn Bhd / Nuranissa Hanim Muhammad Rozi - Muhammad Rozi, Nuranissa Hanim (2020)
Joje Travel Sdn Bhd is a company which sells travel and outdoor equipment and gears. One of the latest released products by Joje Travel Sdn Bhd is the GoEasy. GoEasy is a battery- operated toiletry bottle equipped with automated dispenser and multi-compartments. Although toiletry bottles are commonly produced and can easily be purchased anywhere, GoEasy on the other hand, is not an ordinary toiletry bottle that we can see in the current market. Our main aim of this product besides than enhancing its multifunctional use, is to ease the product usage, ensuring the best quality of the product and customers’ experience while producing minimal and stylish design. Travelling with different separate toiletry bottles for each toiletry is undeniably space and time-consuming. These bottles also contribute to the extra weight of their bag. Due to that, after observing and doing some research, we have come out with GoEasy toiletry bottle to improve users’ experience. With the increasing people’s interest on activities like travelling, backpacking or hiking, products like GoEasy with various benefits are high in demand along with the design of the bottle which aimed to give a whole better travel experience for its users. We will be putting travellers/backpackers and students as our target customer as they are the people that are potentially be making use of this product the most. Additionally, we will be focusing on Shah Alam as our base market with a physical store located in Section 16, Shah Alam. The price of the product is at a reasonable and affordable point which is RM 14.50.